PENGENALAN BENTUK GEOMETRI DALAM PEMBELAJARAN MELALUI PERMAINAN PUZZLE PADA ANAK USIA 3-4 TAHUN - Widariyati, Widariyati; Syukri, M; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:This research is based on the problem of children aged 3-4 years in PAUD Laskar Pelangi Kubu Raya district where most of the children who become the subject of this research can not mention the forms of geometry, showing the forms of geometry and distinguish the forms of geometry Form of research this is a classroom action research using the puzzle game method. The subjects of this study were children who numbered 12 children. The location used as this research is PAUD Laskar Pelangi Kubu Raya District. Based on the results of research that has been done and after held data analysis, can generally be concluded that through the game puzzle can improve the ability of children in recognizing geometric shapes. Keyword : Introduction of geometry shapes, puzzle games, childhood 3-4 years